PENGGUNAAN MEDIA BUKU PANDUAN MENGGAMBAR TEMA DIRIKU TERHADAP KEMAMPUAN KREATIVITAS ANAK DENGAN GANGGUAN OBESITAS (STUDI EKSPERIMEN DI RA AL-MUTTAQIN KECAMATAN TAWANG KOTA TASIKMALAYA) - Neli Vitriyani Syarifah, - (2022)
The research is motivated by a problem based on the results of a preliminary study at the RA Al-Muttaqin school, namely in the learning process the use LKDP (Student Worksheet) is limited so that there is one child who is still not able to be creative in drawing activities and has obesity disorder. The purpose of this study is to find out how effective the use of the self-themed drawing guidebook is to increase the creativity of children with obesity disorder. The research method used to assist in the data collection process in this research is quantitative through a Single Subject Research approach wotth ab A-B-A research design pattern. The results obtained in this study, namely in the baseline-1 staage (A-1) obtained a total score of 77 with an average percantage of 45,8%, the intervention stage (B) obtained a total score of 290 with an average percentage of 74,0%, and in the baseline-2 (A- 2) stage, the total score was 139 with an average percantage of 82,7%. Thus, the use of the self-themed drawing guidebook is effective and can increase the creativity of children with obesity disorder. Keywords : Media Drawing Guide The Theme Of Myself, Creative Abilities, and Children with Obesity Disorder.